STHE PROBLEMS OF DETERMINING GUILT IN DOMESTIC LEGISLATION, CORRESPONDING TO THE PRINCIPLES OF MODERN CRIMINAL LAW POLICY................. - Жанна, Уалиева (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
In article on an example of the criminal legislation of CIS countries and the Republic of Kazakhstan the problem of definition of fault is considered, the author studied concepts existing in the criminal and legal theory and the content of fault, definition of forms and types of fault as questions of compliance of standards of the criminal law fixing guilty responsibility to the conventional principles of criminal law are analysed.